Automatic calibration of a hydrologic model for simulating groundwater table fluctuations on farms in the everglades agricultural area of south Florida - Kwon, Ho-Young; Grunwald, S.; Beck, H.; Jung, Yunchul (Wiley, 2014)
The Shuffled Complex Evolution—Universal Algorithm (SCE-UA) is an automatic calibration algorithm that has shown success in finding a globally optimum objective function with more efficiency than other methods. We incorporated the SCE-UA into our novel modeling environment, utilizing an ontology-based simulation (OntoSim-Sugarcane) framework adapted to analyze groundwater table (WT) fluctuations and drainage practices on four farm basins in the Everglades Agricultural Area of south Florida.